Current Status and Challenges of Safety Education for Children, Including Those Requiring Medical Care, in Japanese General Schools: Focusing on Disasters - Tomoko Yamamoto (MDPI AG, 2020)
This paper discusses school safety mainly in relation to safety education and examines measures for the comprehensive development of systems to ensure the safety of children at school, including those requiring medical care. The number of children requiring medical care is increasing in general schools following the promotion of inclusive education. The government of Japan has established the School Health and Safety Act and Guidelines on School Curricula. Municipalities have developed education systems that cover the safety education specified in disaster preparedness plans for schools. Safety education has been promoted through problem-oriented and experience-based methods as well as other methods of learning to date. Considering the outcomes of these systems and approaches, it is expected that safety management systems in schools, especially general schools that include children requiring medical care, will also develop in combination with safety education.